La heterogeneidad ambiental en un matorral xerofilo - Santibañez-Andrade, G.=700 1 Castillo Arguero, S.; Zavala-Hurtado, J.A.; Martinez Orea, Y.; Hernandez Apolinar, M.
(Es, En)
Ilus., 44 ref.
Keywords: RESERVAS NATURALES; COMPOSICION BOTANICA; DISTRIBUCION DE LA POBLACION; POBLACION VEGETAL; MEXICO; SOCIEDAD BOTANICA DE MEXICO